Nanoconjugates of a calixresorcinarene derivative with methoxy poly(ethylene glycol) fragments for drug encapsulation - Ermakova, Alina M.; Morozova, Julia E.; Shalaeva, Yana V.; Syakaev, Victor V.; Gubaidullin, Aidar T.; Voloshina, Alexandra D.; Zobov, Vladimir V.; Nizameev, Irek R.; Bazanova, Olga B.; Antipin, Igor S.; Konovalov, Alexander I. (Beilstein Journal of Nanotechnology, 2018)
In order to obtain a non-toxic amphiphilic calixresorcinarene capable to form nanoconjugates for drug encapsulation, tetraundecylcalixresorcinarene functionalized by methoxy poly(ethylene glycol) chains has been synthesized. The macrocycle obtained is characterized by low hemotoxicity. In aqueous solution it forms nanoassociates that are able to encapsulate organic substrates of different hydrophobicity, including drugs (doxorubicin, naproxen, ibuprofen, quercetin). The micelles of the macrocycle slowed down the release of the hydrophilic substrates in vitro. In physiological sodium chloride solution and phosphate-buffered saline, the micelles of the macrocycle acquire thermoresponsive properties and exhibit a temperature-controlled release of doxorubicin in vitro. The combination of the low toxicity and the encapsulation properties of the obtained calixresorcinarene–mPEG conjugate shows promising potential for the use as a supramolecular drug-delivery system.
Keywords: calixresorcinarene; drug encapsulation; hemotoxicity; methoxy poly(ethylene glycol); temperature-controlled release

(untitled) - Kaur, P.; Garg, T.; Rath, G.; Murthy, R. S. R.; Goyal, A. K. (Drug Delivery, 2016)

(untitled) - Allen, T. M.; Cullis, P. R. (Adv. Drug Delivery Rev., 2013)

(untitled) - Martin, C.; Aibani, N.; Callan, J. F.; Callan, B. (Ther. Delivery, 2016)

(untitled) - Webber, M. J.; Langer, R. (Chem. Soc. Rev., 2017)

Calixarenes: an Introduction - Gutshe, C. D. (Royal Society of Chemistry, 2008)

(untitled) - Morozova, J. E.; Syakaev, V. V.; Kazakova, E. K.; Shalaeva, Y. V.; Nizameev, I. R.; Kadirov, M. K.; Voloshina, A. D.; Zobov, V. V.; Konovalov, A. I. (Soft Matter, 2016)

(untitled) - Mironova, D. A.; Muslinkina, L. A.; Syakaev, V. V.; Morozova, J. E.; Yanilkin, V. V.; Konovalov, A. I.; Kazakova, E. K. (J. Colloid Interface Sci., 2013)

(untitled) - Syakaev, V. V.; Kazakova, E. K.; Morozova, J. E.; Shalaeva, Y. V.; Latypov, S. K.; Konovalov, A. I. (J. Colloid Interface Sci., 2012)

(untitled) - Kazakova, E.; Morozova, J.; Mironova, D.; Syakaev, V.; Muslinkina, L.; Konovalov, A. (Supramol. Chem., 2013)

(untitled) - Gorbatchuk, V. V.; Porreva, A. V.; Stepanova, V. B.; Kuzin, Yu. I.; Evtugyn, V. G.; Shamagsumova, R. V.; Stoikov, I. I.; Evtugyn, G. A. (Sens. Actuators, B, 2017)

(untitled) - Gorbachuk, V. V.; Mostovaya, O. A.; Evtugyn, V. G.; Osin, Y. N.; Rizvanov, I. K.; Gerasimov, A. V.; Stoikov, I. I. (Macroheterocycles, 2017)

(untitled) - Tu, C.; Zhu, L.; Li, P.; Chen, Y.; Su, Y.; Yan, D.; Zhu, X.; Zhou, G. (Chem. Commun., 2011)

(untitled) - Yoshida, K.; Fujii, S.; Takahashi, R.; Matsumoto, S.; Sakurai, K. (Langmuir, 2017)

(untitled) - Valkenier, H.; Malytskyi, V.; Blond, P.; Retout, M.; Mattiuzzi, A.; Goole, J.; Raussens, V.; Jabin, I.; Bruylants, G. (Langmuir, 2017)

(untitled) - Mustafina, A.; Zakharova, L.; Elistratova, J.; Kudryashova, J.; Soloveva, S.; Garusov, A.; Antipin, I.; Konovalov, A. (J. Colloid Interface Sci., 2010)

(untitled) - Ten’kovstev, A. V.; Razina, A. B.; Dudkina, M. M. (Polym. Sci., Ser. B, 2014)

(untitled) - Drakalska, E.; Momekova, D.; Manolova, Y.; Budurova, D.; Momekov, G.; Genova, M.; Antonov, L.; Lambov, N.; Rangelov, S. (Int. J. Pharm., 2014)

(untitled) - Momekova, D.; Budurova, D.; Drakalska, E.; Shenkov, S.; Momekov, G.; Trzebicka, B.; Lambov, N.; Tashev, E.; Rangelov, S. (Int. J. Pharm., 2012)

(untitled) - Dria, R. D.; Goudy, B. A.; Moga, K. A.; Corbin, P. S. (Polym. Chem., 2012)

(untitled) - Wu, R.; Al-Azemi, T. F.; Bisht, K. S. (RSC Adv., 2014)

(untitled) - Gou, P.-F.; Zhu, W.-P.; Shen, Z.-Q. (J. Polym. Sci., Part A: Polym. Chem., 2008)

(untitled) - Gao, C.; Wang, Y.; Zhu, W.-p.; Shen, Z.-q. (Chin. J. Polym. Sci., 2014)

(untitled) - Mishra, P.; Nayak, B.; Dey, R. (Asian J. Pharm. Sci., 2016)

(untitled) - Knop, K.; Hoogenboom, R.; Fischer, D.; Schubert, U. S. (Angew. Chem., Int. Ed., 2010)

Small-angle Scattering of X-rays - Guinier, A.; Fournet, G. (Wiley, 1955)

(untitled) - Konarev, P. V.; Volkov, V. V.; Sokolova, A. V.; Koch, M. H. J.; Svergun, D. I. (J. Appl. Crystallogr., 2003)

(untitled) - Svergun, D. I.; Ekström, F.; Vandegriff, K. D.; Malavalli, A.; Baker, D. A.; Nilsson, C.; Winslow, R. M. (Biophys. J., 2008)

(untitled) - Svergun, D. I. (J. Appl. Crystallogr., 1992)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

(untitled) - Zhao, Y. H.; Abraham, M. H.; Zissimos, A. M. (J. Org. Chem., 2003)

(untitled) - Hong, H.; Mai, Y.; Zhou, Y.; Yan, D.; Cui, J. (Macromol. Rapid Commun., 2007)

(untitled) - Fang, Y.; Giesecke, M.; Furó, I. (J. Phys. Chem. B, 2017)

(untitled) - Mohsen-Nia, M.; Rasa, H.; Modarress, H. (J. Chem. Eng. Data, 2006)

(untitled) - Tetko, I. V.; Gasteiger, J.; Todeschini, R.; Mauri, A.; Livingstone, D.; Ertl, P.; Palyulin, V. A.; Radchenko, E. V.; Zefirov, N. S.; Makarenko, A. S.; Tanchuk, V. Y.; Prokopenko, V. V. (J. Comput.-Aided Mol. Des., 2005)

(untitled) - Buchweitz, M.; Kroon, P. A.; Rich, G. T.; Wilde, P. J. (Food Chem., 2016)

(untitled) - Tunstad, L. M.; Tucker, J. A.; Dalcanale, E.; Weiser, J.; Bryant, J. A.; Sherman, J. C.; Helgeson, R. C.; Knobler, C. B.; Cram, D. J. (J. Org. Chem., 1989)

(untitled) - Shuai, X.; Ai, H.; Nasongkla, N.; Kim, S.; Gao, J. (J. Controlled Release, 2004)

(untitled) - He, Y.; He, W.; Liu, D.; Gu, T.; Wei, R.; Wang, X. (Polym. Chem., 2013)

(untitled) - Voloshina, A. D.; Semenov, V. E.; Strobykina, A. S.; Kulik, N. V.; Krylova, E. S.; Zobov, V. V.; Reznik, V. S. (Russ. J. Bioorg. Chem., 2017)

SasView for Small Angle Scattering Analysis

(untitled) - Chen, X.; Ahn, D. U. (J. Am. Oil Chem. Soc., 1998)

(untitled) - Swarbrick, J.; Galownia, J.; Bates, T. R. (J. Colloid Interface Sci., 1972)

(untitled) - Stepankova, J.; Studenovsky, M.; Malina, J.; Kasparkova, J.; Liskova, B.; Novakova, O.; Ulbrich, K.; Brabec, V. (Biochem. Pharmacol., 2011)

(untitled) - Mchedlov-Petrosyan, N. O.; Kholin, Y. V. (Russ. J. Appl. Chem., 2004)